Single Cell RNA Sequencing Reveals the Pathogenesis of Aortic Dissection Caused by Hypertension and Marfan Syndrome - Zhang, Li; Qiu, Zhihuang; Zheng, Hui; Yang, Xi; Ye, Jianqiang; He, Jian; Li, Yumei; Chen, Liangwan (Frontiers in Cell and Developmental Biology, 2022)
Aortic dissection (AD) is mainly caused by hypertension and Marfan syndrome. However, it is unclear whether the cellular components and functions are different between the two causes. 11 aortic samples were collected for single-cell RNA analysis. 20 clusters were disclosed, including VSMCs, Fibroblasts, Endothelial cells, T cells, B cells, Monocytes, Macrophages, Mast cells, and Neutrophils components. There were differences in cell sub-clusters and function between hypertension and Marfan patients. The cells also had different differentiation. Importantly, cell ligand–receptor interactions that were associated with hypertension and Marfan induced AD involving SMC, fibroblast, mo-macrophages and T cell subsets by Cellchat. This study revealed the heterogeneity of cellular components and gene changes in hypertension and Marfan induced AD. Through functional analysis and the changes in intercellular communication, the possible mechanism of different causes of AD was explained from a new perspective, so we can better understand the occurrence and development of diseases.